Feasibility of pancreaticoduodenectomy with synchronous liver metastasectomy for oligometastatic pancreatic ductal adenocarcinoma - A case-control study. (February 2021) - Shao, Yi; Feng, Jiaojiao; Hu, Zhenhua; Wu, Jian; Zhang, Min; Shen, Yan; Zheng, Shusen
Abstract: Background: Resection of pancreatic ductal adenocarcinoma (PDAC) with synchronous liver metastasectomy is still a matter of debate. We aimed to evaluate the feasibility of synchronous resection of PDAC and liver metastases for curative intent at a high-volume surgical center. Methods: Patients who underwent pancreaticoduodenectomy (PD) with synchronous liver metastasectomy (M1 resection group, n = 50) were matched 1 : 1 based on tumor and nodular stage, age, gender, body mass index and concomitant disease with two control groups (M0 resection and M1 no resection). The M0 resection group included patients who underwent PD without metastases. The M1 no resection group included patients with liver metastases who underwent palliative bypass or exploratory laparotomy without resection followed by palliative and adjuvant therapies. Results: M1 resection group had a longer operation time, larger intraoperative blood loss, and longer postoperative hospital stay than other two groups. R0 resection rate of M1 resection group was similar to that of M0 resection group (92% vs. 94%, p = 1.000). Postoperative complications were comparable between the groups. The overall median survival in M1 resection, M0 resection, and M1 no resection group was 16, 30, and 6 months, respectively. Cumulative survival rates for 1-, 2-, and 3-year of the M1 resection, M0 resection, and M1 no resection group were 63.8%, 29.0%, and 6.7%; 94.0%, 74.4%, and 25.1%; 24.0%, 2.0%, and 0%, respectively. The survival of M1 resection group was worse than that of M0 resection group (p = 0.009), however significantly much better than that of M1 no resection group (p = 0.001). Univariate analysis showed carcinoembryonic antigen >8 ng/ml and non-R0 resection were associated with death. Multivariate analysis revealed that M1 resection group had improved survival compared with M1 no resection group. Conclusions: PD with synchronous liver metastasectomy for oligometastatic PDAC is safe and feasible, it might provide survival benefits for selected patients. Highlights: A retrospective, case–control study was conducted at a high-volume surgical center. 50 patients underwent pancreaticoduodenectomy with synchronous liver metastasectomy. Complications were similar in M1 resection, M0 resection and M1 no resection groups. Carcinoembryonic antigen >8 ng/ml and non-R0 resection were associated with death. The survival of M1 resection group was much better than that of M1 no resection.